2017
DOI: 10.1136/bmjqs-2016-005570
|View full text |Cite
|
Sign up to set email alerts
|

Can patient involvement improve patient safety? A cluster randomised control trial of the Patient Reporting and Action for a Safe Environment (PRASE) intervention

Abstract: ObjectiveTo evaluate the efficacy of the Patient Reporting and Action for a Safe Environment intervention.DesignA multicentre cluster randomised controlled trial.SettingClusters were 33 hospital wards within five hospitals in the UK.ParticipantsAll patients able to give informed consent were eligible to take part. Wards were allocated to the intervention or control condition.InterventionThe ward-level intervention comprised two tools: (1) a questionnaire that asked patients about factors contributing to safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
149
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(169 citation statements)
references
References 30 publications
(31 reference statements)
1
149
0
10
Order By: Relevance
“…Resilience in healthcare has previously been described and understood mainly from organisational and staff perspectives 26–28 57. This study has thus offered an increased understanding of patients as agents of resilience and we have highlighted where there are opportunities to strengthen resilience, for example through facilitating patient reporting of safety concerns 58. Using resilience as a theoretical concept to explore patient interventions to prevent errors has provided a view of patients as integral system components, rather than as recipients of treatment in a healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience in healthcare has previously been described and understood mainly from organisational and staff perspectives 26–28 57. This study has thus offered an increased understanding of patients as agents of resilience and we have highlighted where there are opportunities to strengthen resilience, for example through facilitating patient reporting of safety concerns 58. Using resilience as a theoretical concept to explore patient interventions to prevent errors has provided a view of patients as integral system components, rather than as recipients of treatment in a healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies, including those involving patient-initiated and family-initiated rapid response systems, suggest a potential safety benefit,612 others lack definitive evidence 26. But are we using the right yardsticks?…”
Section: Change the Researchmentioning
confidence: 99%
“…The components of the intervention have been reported in detail elsewhere,8 as have the results of the randomised controlled trial which demonstrated no statistically significant effect between the intervention and control wards 9. A feasibility study was undertaken prior to commencement of the full RCT and details of our logic model and moderating factors are reported in the feasibility write up 7.…”
Section: Introductionmentioning
confidence: 99%